Responses of Phospholipase D and Antioxidant System to Mechanical Wounding in Postharvest Banana Fruits - Li Li; Xuemei He; Jian Sun; Changbao Li; Dongning Ling; Jinfeng Sheng; Fengjin Zheng; Guoming Liu; Jiemin Li; Yayuan Tang; Ping Yi; Ming Xin; et al. (Journal of Food Quality)
Banana fruits are susceptible to mechanical damage. The present study was to investigate the responses of phospholipase D (PLD) and antioxidant system to mechanical wounding in postharvest banana fruits. During 16 d storage at 25°C and 90% relative humidity, PLD activity in wounded fruits was significantly higher than that in control (without artificial wounding fruits). The higher value of PLD mRNA was found in wounded fruits than in control. PLD mRNA expression reached the highest peak on day 4 in both groups, but it was 2.67 times in wounded fruits compared to control at that time, indicating that PLD gene expression was activated in response to wounding stress. In response to wounding stress, the higher lipoxygenase (LOX) activity was observed and malondialdehyde (MDA) production was accelerated. The activities of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and ascorbate peroxidase (APX) in wounded fruits were significantly higher than those in control. The concentrations of reactive oxygen species (ROS) such as superoxide anion (O2•-) and hydrogen peroxide (H2O2) in fruits increased under mechanical wounding. The above results provided a basis for further investigating the mechanism of postharvest banana fruits adapting to environmental stress.